EXPERIMENTAL INVESTIGATION OF SOME MECHANICAL PROPERTIES OF RUBBERIZED CONCRETE WITH HIGHEST POSSIBLE RUBBER CONTENT - ABDULLAH, WRYA A.; MUHAMMAD, MUHAMMAD A.; ABDULKADIR, MOHAMED R. (Journal of Duhok University, 2021)
Each year more than a billion tires are discarded globally, millions of them are disposed to landfills especially in the developing countries which leads to serious environmental issues. This paperexperimentally investigates mechanical properties of concrete containing highest possible ratio of recycledtire rubber content as fine aggregate replacement in terms of compressive strength, workability, dry and fresh densities. For this purpose, eleven different concrete mixes were cast with various sand replacement ratios by mass from 0% to 60% with increments of 6%. Three cubic specimens from each mix were cast and tested to measure the mechanical properties at the age of 28 days. All the specimens had thewater-cement ratio and curing period without using any admixtures. It is concluded that the workability, density, and compressive strength of the rubberized concrete samples are significantly reduced with an increase of the rubber content. Moreover, it is observed that the mix becomes stiff and non-workable beyond 60% of rubber content. Furthermore, the test results are compared with non-rubberized concrete (control mix) and the available data on rubberized concrete from the literature. Finally, equations for predicting the aforementioned properties are derived.